Análisis comparativo del diseño hidráulico del desvío de cauces con túnel, mediante teoría básica y la herramienta computacional Hec Ras (2020)
In the state-of-the-art design of tunnel-type diversion works for channels in the construction of dams, the hydraulic design of this type of works is commonly carried out using spreadsheets programmed with the basic design theory and physical modeling of the work. . The present work sought to compare the results obtained with the analysis of the basic theory and the use of the Hec-Ras computational tool. For this, the basic theory of diversion tunnel design and the fundamental concepts used by the Hec-Ras computational tool are initially described.